Ovicidal effect of essential oils from Zingiberaceae plants and Eucalytus globulus on eggs of head lice, Pediculus humanus capitis De Geer - Soonwera, Mayura; Wongnet, Orawan; Sittichok, Sirawut (My University, 2018)
Background: Head lice infestation is an important public health problem worldwide. Chemical pediculicides have lost their efficacy because lice have developed resistance to them. Therefore, alternative pediculicides such as essential oils and herbal products have been proposed for treating head lice infestation. Study design: To determine the efficacy of essential oils from three Zingiberaceae plants (Curcuma xanthorrhiza, Curcuma zedoaria and Zingiber zerumbet) against head lice eggs and to investigate an augmenting substance (Eucalyptus globulus EO) for improving the efficacy of these essential oils in killing head lice eggs, especially on the inhibition of their hatching process. Permethrin pediculicide, soyabean oil, and drinking water were used as positive, negative, and neutral controls, respectively. Methods: An immersion test was used to evaluate the ovicidal activity of 12 essential oil formulations. Head lice eggs were immersed for 1, 5 and 10 min in the treatments. Mortality rate was observed on day 7 and day 14; mortality was checked under a stereomicroscope. Results: All head lice eggs that were immersed in a combination of 10% C. zedoaria EO and 10% E. globulus EO for 5 min did not hatch at all for 7–14 days of incubation. All head lice eggs that were immersed in soyabean oil and drinking water for 1, 5, and 10 min showed 100% hatching rate in 7–14 days of incubation. All head lice eggs that were immersed in permethrin pediculicide for 1, 5 min, showed 100% hatching rate, but when they were immersed for 10 min, permethrin provided 4.0–6.0% inhibition rate with 94.0–96.0% hatching rate for 7–14 days of incubation. All combinations of Zingiberaceae EOs and E. globulus EO at low and high concentrations (5 and 10%) exhibited high ovicidal activities against head lice eggs, and the combinations showed a synergistic effect with an increase in the inhibition rate of more than 50%. Conclusion: These results demonstrated that Zingiberaceae EOs augmented with E. globulus EO are promising ovicidal agents for head lice control.
Keywords: Eucalyptus globulus EO; Head lice egg; Ovicidal activity; Zingiberaceae EOs